2020
DOI: 10.29121/granthaalayah.v7.i10.2019.399
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic and Biological Utility of 2,3-Dichloro-1,4-Naphthoquinone: A Review

Abstract: 2,3-Dichloro-1,4-naphthoquinones (dichlone) have attracted considerable attention for the construction of biologically active tricyclic and tetracyclic 1,4-quinones and other derivatives. A diversified reaction of 2,3-dichloro-1,4-naphthoquinones such as cycloaddition, condensation, photo induced and nucleophilic substitution reactions with suitable nucleophiles viz. carbon, nitrogen, oxygen, sulfur, selenium etc have been explored. Various synthesized compounds have also explored for their biological activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 130 publications
0
2
0
1
Order By: Relevance
“…This compound can be used as solidstate fluorescence material (Figure 13) [60]. The nucleophilic substitution of 2,3-dichloro-1,4-naphthoquinone is a synthetic strategy for introducing nitrogen, oxygen, carbon, sulfur, and selenium nucleophiles at C2 and C3 positions [61].…”
Section: Chemical Modification Of Nqs Structures With Nitrogen Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…This compound can be used as solidstate fluorescence material (Figure 13) [60]. The nucleophilic substitution of 2,3-dichloro-1,4-naphthoquinone is a synthetic strategy for introducing nitrogen, oxygen, carbon, sulfur, and selenium nucleophiles at C2 and C3 positions [61].…”
Section: Chemical Modification Of Nqs Structures With Nitrogen Groupsmentioning
confidence: 99%
“…Campora et al (2021) reported the synthesis of NQ derivatives bearing hydrophobic moieties as promising candidates for Alzheimer's disease therapy [62]. Mahalap- The nucleophilic substitution of 2,3-dichloro-1,4-naphthoquinone is a synthetic strategy for introducing nitrogen, oxygen, carbon, sulfur, and selenium nucleophiles at C2 and C3 positions [61].…”
Section: Chemical Modification Of Nqs Structures With Nitrogen Groupsmentioning
confidence: 99%
“…2,3-Дихлор-1,4-нафтохинон (NQ, торговое название дихлон) (рис. 1а) является одним из важнейших производных 1,4-нафтохинона, и в современной химии используется как ключевой промежуточный продукт в синтезе новых 1,4-нафтохинонов, обладающих различными фармакологическими свойствами [15][16][17][18].…”
Section: Introductionunclassified